Improving Wudhu Skills Through Pesantren Learning - Maimun, Maimun; Hamdani, Hamdani (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Pesantrens as Islamic educational institutions are ideal if their education system teaches spiritual activities and worship, including pre-worship activities with wudhu. This research examines the application of Pesantren education in improving the wudhu skills of students in the small Pesantren Hidayatun Najah Samiran Proppo Pamekasan. The study used a qualitative method with a case study approach at the small Pesantren Hidayatun Najah. The data sources used are the person in charge of the eastern boarding school, administrators and students, while the secondary data sources are data that supports the main source. Data collection in this study was interviews, observation and documentation, data analysis was carried out using a process of data condensation, data presentation and drawing conclusions. In checking the validity of the data, this study used source triangulation to compare data obtained from various informants to strengthen the validity of the data. The results of this research show that the Hidayatun Najah small cottage improves wudhu skills using theory-based teaching and instruction, the implementation of both activities is carried out based on the activity structure in the small cottage. The most important finding in this study is the implementation of learning in small huts, namely by using theoretical and practical models in improving students' wudhu skills. This study can be a reference medium for Pesantrens in improving wudhu skills for their students.